DESAIN KEMASAN PRODUK MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT PADA UKM TAHU DI BATAM - Santi Siahaan; Sirait, Ganda (Computer Science and Industrial Engineering, 2022)
Tofu Sari Rasa factory, which is located in Tanjung Piayu, Batam, produces high-quality food. The main product is tofu sumedang. The purpose of this research is to identify consumer needs and desires, as well as to determine the Voice of the Customer by distributing questionnaires to consumers using the Quality Function Deployment (QFD) method. The respondents of the study are Tofu Sari Rasa Factory customers. According to the findings, the characteristics of respondents based on age were at most 26-40 years (62.5 %), women (77.5 %), high school/diploma (67.5 %), housewives (27.5 %), information on consuming the most (85 %), information on buying the most (80 %), information from consumers who have bought and consumed the most (65 %), the frequency of purchases at most >2 times (65 %), and the problem barriers that affect interest in buying the most in less attractive packaging (67.5 %). The packaging of the product with a high priority has halal information on it, with a score of 5, whereas the packaging of the product with a low priority has sufficient thickness and expired information, with a score of 2. According to the results, the highest technical importance rating prioritizes all information. packaging received a score of 494, followed by 247 absolute importance and 22 % relative importance. Giving the production address receives the lowest technical importance rating of 72, with absolute importance of 36. Based on the findings, the conclusions in this research are several packaging design criteria, such as attractive packaging colors, durability, product size, sufficient thickness, comfortable to grip, easy to carry packaging, manufacturer's address on the packaging, weight the product is clean, there is halal information, the product description is easy to read, and the logo on the packaging is made attractive.